CMOS Transceiver Epiretinal Vision Restoration Retina Chipset using Wireless Inductive Coupling - Telagathoti Pitchaiah, Gajula Ramana Murthy, Hima Bindu Katikala (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In medical implants the inductive coupling is the most common topology used for power transfer. Because of design complexity a wireless power transfer is mostly adaptable in the medical implants. In this paper, for the data progressing inside the implant a complementary metal oxide semiconductor transceiver (CMOS TRx) on-chip prototype is proposed with an inductive coupling power transfer for retina application. The CMOS TRx is an integrated device contains the data modulators, configured inductive, demodulator & epiretinal electrode array used to generate an action potential inside the retina. The binary phase shift modulator with class-E power amplifier is designed to transfer the data within two carrier cycles at the transmitter side to maintain high modulation rate than other modulation techniques. The proposed inductive coupling tuned to be resonant at the frequency of 13.56MHz as same as bpsk carrier frequency with more parallel receiver resonance (ωp) by considering the retina permittivity.